The Role of Building Regulation as a Policy Instrument for Accelerating the Transition to a Low Carbon Built Environment - Enker, Robert Abraham (Curtin University, 2020)
Appreciating the pivotal role of the building sector is crucial to an effective response to climate change. Implementation of policies for mitigating greenhouse emissions from the world’s buildings invariably relies on regulatory, economic or informational instruments. In fact a comprehensive strategy utilizing all three approaches is required; although regulatory measures - building energy codes - are demonstrably most effective. Successful building energy policy must draw upon Behavioural Economics to achieve desired changes in stakeholder behaviour.